2000
DOI: 10.1111/1467-9469.00217
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of a Growth Curve Model with a General Autoregressive Covariance Structure

Abstract: In this paper we consider from maximum likelihood and Bayesian points of view the generalized growth curve model when the covariance matrix has a Toeplitz structure. This covariance is a generalization of the AR(1) dependence structure. Inferences on the parameters as well as the future values are included. The results are illustrated with several real data sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…MLE for growth curve models is embedded in commercial statistical packages, such as SAS PROC MIXED and PROC NLMIXED and Splus LME and NLME. Recently, Bayesian methods have received more attention as useful tools for estimating a variety of models including growth curve models, in particular complex growth curve models which can be difficult or impossible to estimate in the current MLE-based software (Lee & Chang, 2000;Lee & Liu, 2000;McArdle & Wang, in press;Menzefricke, 1998;Pettitt, Tran, Haynes, & Hay, 2006;Seltzer, Wong, & Bryk, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…MLE for growth curve models is embedded in commercial statistical packages, such as SAS PROC MIXED and PROC NLMIXED and Splus LME and NLME. Recently, Bayesian methods have received more attention as useful tools for estimating a variety of models including growth curve models, in particular complex growth curve models which can be difficult or impossible to estimate in the current MLE-based software (Lee & Chang, 2000;Lee & Liu, 2000;McArdle & Wang, in press;Menzefricke, 1998;Pettitt, Tran, Haynes, & Hay, 2006;Seltzer, Wong, & Bryk, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Scheines et al (1999) showed that Bayesian estimation outperforms ML estimation when sample size is small. Lee and Chang (2000) demonstrated that the MCMC algorithm provides a smaller prediction error such as the mean squared deviation and is slightly more efficient with small sample growth data.…”
mentioning
confidence: 99%
“…SAS NLMIXED uses maximum likelihood estimation (MLE) and is limited to handling two-level data; Mplus uses MLE, robust weighted least squares, and other methods; and WinBUGS uses Bayesian methods. In particular, complex growth curve models can be difficult or impossible to estimate using current MLE-based software (J. C. Lee & Chang, 2000; J. C. Lee & Liu, 2000;McArdle & Wang, 2006;Menzefricke, 1999;Pettitt, Tran, Haynes, & Hay, 2006;. Bayesian methods have been widely applied in time series contexts and have played a significant role in recent developments in error correction and stochastic volatility models (Congdon, 2003).…”
Section: Level 2 Modelmentioning
confidence: 99%